Heart Failure Association of the ESC, Heart Failure Society of America and Japanese Heart Failure Society Position statement on endomyocardial biopsy - Seferović, Petar M; Tsutsui, Hiroyuki; McNamara, Dennis M; Ristić, Arsen D; Basso, Cristina; Bozkurt, Biykem; Cooper, Leslie T; Filippatos, Gerasimos; Ide, Tomomi; Inomata, Takayuki; Klingel, Karin; Linhart, Aleš; et al. (European journal of heart failure, 2021)
Endomyocardial biopsy (EMB) is an invasive procedure, globally most often used for the monitoring of heart transplant (HTx) rejection. In addition, EMB can have an important complementary role to the clinical assessment in establishing the diagnosis of diverse cardiac disorders, including myocarditis, cardiomyopathies, drug-related cardiotoxicity, amyloidosis, other infiltrative and storage disorders, and cardiac tumours. Improvements in EMB equipment and the development of new techniques for the analysis of EMB samples have significantly improved diagnostic precision of EMB. The present document is the result of the Trilateral Cooperation Project between the Heart Failure Association of the European Society of Cardiology, the Heart Failure Society of America, and the Japanese Heart Failure Society. It represents an expert consensus aiming to provide a comprehensive, up-to-date perspective on EMB, with a focus on the following main issues: (i) an overview of the practical approach to EMB, (ii) an update on indications for EMB, (iii) a revised plan for HTx rejection surveillance, (iv) the impact of multimodality imaging on EMB, and (v) the current clinical practice in the worldwide use of EMB.
Keywords: Cardiac tumours; Cardiomyopathy; Cardiotoxicity; endokard; Sarcoidosis; Endocardium; Endomyocardial biopsy; Biopsy; Heart Transplantation; Amyloidosis; Heart failure; Myocarditis; Japonsko; myokard; Humans; Heart transplantation; Myocardium; Japan; srdeční selhání; biopsie; transplantace srdce; Heart Failure; lidé